Perinatal outcomes after admission with COVID-19 in pregnancy: a UK national cohort study - Engjom, HM; Ramakrishnan, R; Vousden, N; Bunch, K; Morris, E; Simpson, N; Gale, C; O'Brien, P; Quigley, M; Brocklehurst, P; Kurinczuk, JJ; Knight, M (Springer Nature, 2024)
There are few population-based studies of sufficient size and follow-up duration to have reliably assessed perinatal outcomes for pregnant women hospitalised with SARS-CoV-2 infection. The United Kingdom Obstetric Surveillance System (UKOSS) covers all 194 consultant-led UK maternity units and included all pregnant women admitted to hospital with an ongoing SARS-CoV-2 infection. Here we show that in this large national cohort comprising two years’ active surveillance over four SARS-CoV-2 variant periods and with near complete follow-up of pregnancy outcomes for 16,627 included women, severe perinatal outcomes were more common in women with moderate to severe COVID-19, during the delta dominant period and among unvaccinated women. We provide strong evidence to recommend continuous surveillance of pregnancy outcomes in future pandemics and to continue to recommend SARS-CoV-2 vaccination in pregnancy to protect both mothers and babies.